Effect of training surface on acute physiological responses following interval training - Binnie, M.; Peeling, P.; Pinnington, H.; Landers, G.; Dawson, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
This study compared the effect of sand and grass training surfaces during a common pre-season interval training session in well-trained team sport athletes (n=10). Participants initially completed a preliminary testing session to gather baseline (BASE) performance data for vertical jump (VJ), repeated sprint ability (RSA) and a 3 km running time trial (RTT). Three days subsequent to BASE, all athletes completed the first interval training session, which was followed by a repeat of the BASE performance tests the following day (24 h post-exercise). Seven days later, the same interval training session was completed on the opposing surface, and was again followed 24 h later by the BASE performance tests. During each session, blood lactate (BLa), ratings of perceived exertion (RPE) and heart rate (HR) were recorded. Additionally, venous blood was collected pre-, post-, and 24 h post-exercise, and analysed for serum concentrations of Myoglobin (Mb), Creatine Kinase (CK), Haptoglobin (HP) and C-Reactive Protein (CRP). Results showed significantly higher BLa and HR responses experienced during the SAND session (p<0.05), with no differences observed between surfaces for the blood markers of muscle damage, inflammation and hemolysis (p>0.05). Twenty-four hours later, the RTT was performed significantly faster following the SAND session compared to GRASS (p=0.001). These results suggest that performing interval training on a sand (versus grass) surface can result in a greater physiological response, and less decrement in next day endurance performance.